Yield enhancement of recombinant α-Amylases in Bacillus amyloliquefaciens by ARTP mutagenesis-screening and medium optimization - Xu, Ting-Liang; Jing, Peng; Zhu, Yu-Ling; Su, Li; Zhou, Kai-Yan; Cheng, Hai-Na; Tang, Shi-Zhe; Zhou, Hong-Bo (Penerbit Universiti Kebangsaan Malaysia, 2019)
α-Amylase is the most extensively applied enzyme in industry. There is an urgent need for improvement on the yield of α-amylases currently. Herein, a strategy which combined Atmospheric and Room Temperature Plasma (ARTP) mutagenesis tool for construction of mutant library of Bacillus amyloliquefaciens with a 24-well plates screening technique was adopted to improve the yield of recombinant Bacillus amyloliquefaciens α-amylases (BAA). A mutant strain named B. amyloliquefaciens ZN mut-7# was obtained, and the activity of BAA produced by this mutant strain was 86.92% higher than that of the original strain. B. amyloliquefaciens ZN mut-7# has an unchanged BAA gene and genetic stability. This successful application proved that ARTP can be applied to the genetically engineering strains that contain recombinant plasmid. Furthermore, response surface methodology offers an achievable and efficient strategy to optimize the composition of medium used to generate BAA in B. amyloliquefaciens ZN mut-7#. A 1.28-fold increase had been obtained compared to the production of non-optimized fermentation medium. This study demonstrates that ARTP mutagenesis and medium optimization are efficient and feasible methods for increasing recombinant enzyme production in the genetically engineering strains.